Reflections on Rasheda L. Weaver's book “Social entrepreneurship. A practical introduction” - A.A. Atanasova (Векторы благополучия: экономика и социум)
The article is written as reflections on the book by R.L. Weaver "Social entrepreneurship. A practical guide", published in the USA in 2023. The book offers another approach to studying the phenomenon of social entrepreneurship, and also provides a step‐by‐step plan for creating a social enterprise for specialists to change their communities. Aim. To analyze the foreign experience and assess the possibility of using this experience in Russia. To achieve this aim the author has analyzed the content of R.L. Weaver's book and highlighted its scientific novelty, as well as the possibilities of applying a new approach to studying the phenomenon in Russia. Relevance. This book is the first educational methodological manual for self‐study. Methods. Secondary data analysis method. The possibilities of applying R.L. Weaver's approach in Russia include: consideration of the book as a textbook for self‐study of the subject from both theoretical and practical points of view; following one of the models of social enterprise when starting a social enterprise; using the business plan scheme for a social enterprise described in the book. The book will be useful for scholars studying social entrepreneurship, social entrepreneurs, and people who want to become social entrepreneurs.